Delirium associated with olanzapine therapy in a patient with Bipolar Affective Disorder: A Case Report - Shrestha, R.; Singh, P.M.; Joshi, N.; Dhonju, G. (Journal of Psychiatrists’ Association of Nepal, 2017)
A patient of Bipolar Affective Disorder (BPAD) developed delirium after initiation and increment in the dosage of olanzapine. After hospital admission, we started olanzapine in combination with lithium. Olanzapine was gradually increased to 30 mg/day and lithium gradually increased to 1000 mg/day with serum lithium level at 0.85 mmol/L. After discontinuation of olanzapine, there was a complete resolution of delirium. We, hereby, report the case of delirium associated with olanzapine therapy.